THE EFFECTS OF DIFFERENTIATED INSTRUCTIONAL DESIGN ON STUDENTS' SELF-EFFICACY BELIEFS, METACOGNITIVE SKILLS AND ACADEMIC ACHIEVEMENT - Yabas, Defne; Altun, Sertel (HACETTEPE UNIV, 2009)
This study focuses on differentiated instructional design by investigating the effect of the design on students' metacognitive skills and self efficacy. The research has a pretest-posttest design and the treatment group consists of 25 sixth grade students, who are attending Esenler Cumhuriyet Primary School. Achievement test, developed by the researcher, and metacognitive skills and self efficacy perception scales, which are adapted by Uredi (2005), are implemented twice, before and after treatment. All instruments' reliability and validity analyses had been controlled. The results of the study show that there are significant and positive differences between pretests and posttests of total academic achievement, knowledge, comprehension and application questions, metacognitive skills and self efficacy scores. These results support all the three hypthoseses of the study.
Keywords: Differentiated instructional design; self efficacy; metacognitive skills; academic achievement; mathematics education; Education & Educational Research